Sterling-dollar diplomacy : Anglo-American collaboration in the reconstruction of multilateral trade - Gardner, Richard N. (Oxford : Clarendon Press, 1956)
This book is a history of multilateral goal and of the early life of the institutions which were to make it a reality - the International Monetary Fund and International Bank for Reconstruction and Development; the Anglo-American Financial Agreement; the International Trade Organization; and the General Agreement on Tariffs and Trade
Bibliography: p. [393]-412.
ijb, 15/01/2019
Loans
Keywords: Currency question; International economic relations; United States; Great Britain